The chemical components, action mechanisms, and clinical evidences of YiQiFuMai injection in the treatment of heart failure - Shichao Lv; Shichao Lv; Yunjiao Wang; Wanqin Zhang; Hongcai Shang (Frontiers Media S.A., 2022)
YiQiFuMai injection (YQFM), derived from Shengmai Powder, is wildly applied in the treatment of cardiovascular diseases, such as coronary heart disease and chronic cardiac insufficiency. YiQiFuMai injection is mainly composed of Radix of Panax ginseng C.A. Mey. (Araliaceae), Radix of Ophiopogon japonicus (Thunb.) Ker Gawl (Liliaceae), and Fructus of Schisandra chinensis (Turcz.) Baill (Schisandraceae), and Triterpene saponins, steroidal saponins, lignans, and flavonoids play the vital role in the potency and efficacy. Long-term clinical practice has confirmed the positive effect of YiQiFuMai injection in the treatment of heart failure, and few adverse events have been reported. In addition, the protective effect of YiQiFuMai injection is related to the regulation of mitochondrial function, anti-apoptosis, amelioration of oxidant stress, inhibiting the expression of inflammatory mediators, regulating the expression of miRNAs, maintaining the balance of matrix metalloproteinases/tissue inhibitor of metalloproteinases (MMP/TIMP) and anti-hypoxia.